Chronic hypoxaemia as a molecular regulator of fetal lung development: implications for risk of respiratory complications at birth. (January 2017) - McGillick, Erin V.; Orgeig, Sandra; Giussani, Dino A.; Morrison, Janna L.
Summary: Exposure to altered intrauterine conditions during pregnancy influences both fetal growth and organ development. Chronic fetal hypoxaemia is a common pregnancy complication associated with intrauterine growth restriction (IUGR) that may influence the risk of infants experiencing respiratory complications at birth. There are a variety of signalling pathways that contribute to normal fetal lung development at the molecular level. The specific molecular effects of chronic hypoxaemia associated with IUGR on lung development are likely to be dependent on the specific aetiology (maternal, placental and/or fetal factors) that can alter hormone concentrations, oxygen and nutrient transport to the fetus. This review discusses molecular pathways that may contribute to altered fetal lung maturation following exposure to chronic hypoxaemia. Importantly, these studies highlight that the heterogeneity in respiratory outcomes at birth in this obstetric subpopulation are likely determined by the timing, severity and duration of chronic hypoxaemia encountered by the fetus during pregnancy.